Acute intermittent porphyria case in clinical practice internist - Chopyak, V. V.; Tolstyak, Y. F. (Journal of Education, Health and Sport, 2019)
Porphyria is group of eight metabolic disorders characterized by defects in hemebiosynthesis. The presentation of porphyria is highly variable, and the symptoms are non specific, which accounts in part for delay sinestablishing a diagnosis. Inthisstudy, were port the characteristics of one case acute porphyria patients in Ukraine. Case patient is femal, and the age was 20 years. The most frequent presenting symptoms was abdominal pain, dyspnoe, paresis and convulsion. Hyponatremia was the most common electrolyte abnormality. Testing provided a precise diagnosis of the patients:determination of сoproporphyrins in the urine (the survey was conducted three times) three times the figures were slightly increasing, the highest 172 (provision do 120)nmol / day,determination of porphyrins in the blood of 248.5 (rule 60) mcmol / day and intheurine of 422 mcg / L (normal 150mcg / L), and excretion in the urine δ-aminolevolinovoyacid 700 (normal 8-53) mcmol / day. Treatment. Drugs for the treatment of porphyria are not registered in Ukraine, because patients in stable condition was transferred to the Department of porphyria treatment Institute of Hematology and Transfusion (Warsaw, Poland).